2015
DOI: 10.4103/1008-682x.150845
|View full text |Cite
|
Sign up to set email alerts
|

Is serum sex hormone-binding globulin a dominant risk factor for metabolic syndrome?

Abstract: This multi-center, cross-sectional study investigated the association between serum testosterone (T) levels, serum sex hormone-binding globulin (SHBG) levels, and the risk of metabolic syndrome (MS) in 3332 adult Chinese men. The prevalence of MS was 34.7%, and men with MS had lower serum levels of total T (TT) and SHBG than those without MS (P < 0.001). There was no significant difference in serum free T (FT) levels between subjects with and without MS (P = 0.627). In logistic regression analysis, the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“… 23 , only TT and SHBG, but not FT were significant predictors for the risk of incident MetS in men. These results suggest that the impact of FT on MetS may be weak or confounded by several factors like discrepancy in the measurement of FT, definition of MetS and baseline characteristics of the different study populations 15 , 16 , 24 . Further studies are needed to clarify the real relationship between FT and MetS.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“… 23 , only TT and SHBG, but not FT were significant predictors for the risk of incident MetS in men. These results suggest that the impact of FT on MetS may be weak or confounded by several factors like discrepancy in the measurement of FT, definition of MetS and baseline characteristics of the different study populations 15 , 16 , 24 . Further studies are needed to clarify the real relationship between FT and MetS.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, both low TT and SHBG were significant predictors for the risk of prevalent MetS, but FT showed no significant association. Several cross-sectional studies also reported no significant difference in FT level between subjects with and without MetS 16 , 19 21 . In the longitudinal studies of Kupelian et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly in this regard, we previously reported that men with low TT had significantly lower serum SHBG levels compared to men with normal TT [18]. It is well established that low SHBG levels are correlated with increased insulin resistance and predict the development of metabolic syndrome [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Both cross-sectional and longitudinal epidemiological studies indicate that the level of SHBG is lower in men with MetS 3840. Other researchers emphasize, however, that the relationships between MetS and either TS or SHBG are stronger in younger men 34,35.…”
Section: Introductionmentioning
confidence: 99%